Value of Autoantibody Expression During Long-Term Follow-Up in Paediatric ALL Patients After Allogeneic Haematopoietic Stem Cell Transplantation - Lawitschka, Anita; Ronceray, Leila; Bauer, Dorothea; Rittenschober, Michael; Zubarovskaya, Natalia; Geyeregger, Rene; Pickl, Winfried F.; Kuzmina, Zoya (Frontiers in Pediatrics, 2021)
Objectives: Chronic graft-versus-host disease (cGvHD) following haematopoietic stem cell transplantation (HSCT) shares many similarities with de novo autoimmune disorders, being associated with the presence of autoantibodies. However, data on the implication of autoantibodies in paediatric HSCT recipients are scarce. In this single-centre study of paediatric patients with acute lymphoblastic leukaemia (ALL) surviving longer than 3 months, our objectives were to evaluate autoantibody expression and investigate the correlation with cGvHD and immune reconstitution using serially monitored parameters. Methods: We investigated circulating autoantibodies together with cellular and humoral parameters [including major T- and B-cell subsets, natural killer (NK) cells, and immunoglobulin levels] in 440 samples from 74 patients (median age 10.9 years, range 2.7–22.2 years) serially during long-term follow-up of median 8 years (range 0.4–19.3 years). Evaluations comprised of patient and transplant characteristics, precisely reviewed details of National Institute of Health (NIH)-defined cGvHD, and outcome data such as relapse, overall survival (OS) and mortality. Analysis of these clinical parameters was performed to identify possible associations. Results: Autoantibodies were detected in 65% (48/74) of patients. Anti-nuclear antibodies were the most common, occurring in 75% (36/48) of patients with autoantibodies. When comparing demographic data and transplant characteristics, there were no significant differences between patients with and without autoantibody expression; 5-year OS was excellent, at 96.4 and 95.8%, respectively. Neither the expression of autoantibodies nor the occurrence of cGvHD correlated with significantly worse OS or relapse rate. Furthermore, there was no significant association between autoantibody profiles and the incidence, overall severity or organ involvement of cGvHD. Patients with autoantibodies showed significantly better immune reconstitution, with overall higher numbers of T cells, B cells, and serum immunoglobulins. In autoantibody-positive patients with cGvHD, autoantibody production positively correlated with the expansion of CD56+ NK cells (236.1 vs. 165.6 × 103 cells/mL, respectively; p = 0.023) and with signs of B-cell perturbation, such as higher CD21low B cells (23.8 vs. 11.8 × 103 cells/mL, respectively; p = 0.044) and a higher ratio of CD21low B cells/CD27+ memory B cells (1.7 vs. 0.4, respectively; p = 0.006) in comparison to autoantibody-positive patients without cGvHD. Furthermore, when assessing the correlation between autoantibody positivity and the activity of cGvHD at time of analysis, indicators of aberrant B-cell homeostasis were substantiated by a lower proportion of CD27+ memory B cells (9.1 vs. 14.9%, respectively; p = 0.028), a higher ratio of class-switched CD27+IgD−/CD27+ memory B cells (3.5 vs. 5.1%, respectively; p = 0.013), significantly elevated numbers of CD21low B cells (36.8 vs. 11.8 × 103 cells/mL, respectively; p = 0.013) and a higher ratio of CD21lowB cells/CD27+ memory B cells (2.4 vs. 0.4, respectively; p = 0.034) in the active vs. the no cGvHD group. We then assessed the potential role of autoantibody expression in the context of elevated CD19+CD21low B cells (cutoff >7%), a well-known marker of cGvHD. Surprisingly we found a significant higher proportion of those cases where elevated CD21low B cells correlated with active cGvHD in samples from the autoantibody-negative group vs. the antibody-positive group (82 vs. 47%, respectively; p = 0.0053). When comparing immune parameters of the large proportion of survivors (89%) with the small proportion of non-survivors (11%), data revealed normalisation within the B-cell compartment of survivors: there were increased numbers of CD27+ memory B cells (54.9 vs. 30.6 × 103 cells/mL, respectively; p = 0.05), class-switched CD27+IgD− B cells (21.2 vs. 5.0 × 103 cells/mL, respectively; p < 0.0001), and immunoglobulin G4 (40.9 vs. 19.4 mg/dL, respectively; p < 0.0001). Overall mortality was significantly associated with an elevated proportion of CD21low B cells (13.4 vs. 8.8%, respectively; p = 0.039) and CD56+ NK cells (238.8 vs. 314.1 × 103 cells/mL, respectively; p = 0.019). In multivariate analysis, better OS was significantly associated with lower numbers of CD56+ NK cells [hazard ratio (HR) 0.98, p = 0.041] and higher numbers of CD27+ memory B cells [(HR) 1.62, p = 0.014]. Conclusion: Our data shows that autoantibody profiles are not suitable biomarkers for diagnosing cGvHD in children or for predicting cGvHD severity, disease course and outcome. We identified a number of indicators of aberrant immune homeostasis associated with active cGvHD in paediatric ALL patients after HSCT. These findings confirm published results and suggest that candidate B cell subpopulations may serve as a surrogate measure for characterisation of cGvHD in paediatric HSCT for malignant diseases, and warrants confirmation in larger, multicentre studies.